The evolution of Islamic finance in the digital age: Analyzing asset growth patterns and stakeholder attitudes in emerging market economies - Muin, Rahmawati; Syamsuri, Helmy; Syamsiah, Syamsiah; Fauziah, Fauziah; Possumah, Bayu Taufiq (International Journal of Innovative Research and Scientific Studies, 2025)
This study examines the transformative role of Digital Financial Services (DFS) in the growth and operational efficiency of Islamic Finance Institutions (IFIs) in emerging market economies. By employing a mixed-methods approach, the research combines quantitative financial analysis and qualitative stakeholder insights to assess the impact of DFS on asset growth, customer base expansion, and profitability. The results indicate that DFS has significantly enhanced financial inclusion, particularly in underserved regions, through innovations like mobile banking and digital payments. The analysis reveals a strong correlation between DFS adoption and increased operational efficiency and reduced transaction costs. The research highlights the need for collaboration among regulators, IFIs, and fintech providers to foster sustainable growth and advance financial inclusion. Challenges related to Sharia compliance, regulatory frameworks, and technological infrastructure require targeted strategies for effective DFS implementation. By addressing the identified challenges, DFS has the potential to reshape Islamic finance and contribute significantly to the broader economic development of emerging markets, creating more inclusive and efficient financial systems.